Sensory innervation in porous endplates by Netrin-1 from osteoclasts mediates PGE2-induced spinal hypersensitivity in mice - Shuangfei Ni (Nature Portfolio, 2019)
Spinal pain is a major clinical problem. Here the authors show that osteoclasts create porous area of endplates of the vertebrae and sensory innervation of porous endplates by Netrin-1 release from osteoclasts mediates PGE2-induced spinal hypersensitivity in mice.